(untitled) (Linguist, 2025)
This article explores the concept of critique in the Rhetoric of Audience (RA) in comparison to well-established critical disciplines such as Critical Discourse Analysis (CDA). The article is divided into two parts; the first identifies three characteristics of critique in RA: (1) it combines knowledge and action; (2) it takes the form of a rhetorical response, (3) It is a virtue of resisting communication distortions. These characteristics are based on recalling the linguistic meanings of the term Critique and benefit from contemporary philosophical concepts of criticism, particularly Foucault›s concept of criticism as the virtue of resisting blind obedience. The second part of the article explores the position of RA in Habermas’s critical knowledge classification. It reviews Habermas’s classification of knowledge into natural, hermeneutic, and critical, proposing that AR falls in an undefined intersection of the three categories. It concludes by examining the peculiarities of critique practice in AR compared to CDA that include the concept of practiced critique, its corpus, purpose, and target audiences.